Child care, maternal employment and persistence: A natural experiment from Spain - Natalia Nollenberger; Nuria Rodriguez-Planas (Institute for the Study of Labor (IZA), 2011)
Reconciling work and family is high on many governments' agenda, especially in countries, such as Spain, with record-low fertility and female labor force participation rates. This paper analyzes the effects of a large-scale provision of publicly subsidized child care in Spain in the early 1990s, addressing the impact on mothers' short- and long-run employment outcomes (up to four years after the child was eligible to participate in the program). Exploiting the staggered timing and age-targeting of this child-care expansion, our estimates show that the policy led to a sizable increase in employment (8%), and hours worked (9%) of mothers with age-eligible (3-year-old) children, and that these effects persisted over time. Heterogeneity matters. While persistence is strong among mothers with a high-school degree, the effects of the program on maternal employment quickly fade away among those without a high-school degree. These findings are consistent with the program reducing the depreciation of human capital. The lack of any results among college educated mothers, which represent less than one tenth of mothers, is most likely due to the fact that they are able to pay day care (even when it is mainly privately supplied), and that most of them are already strongly attached to the labor force.
urn:nbn:de:101:1-201108093185
Keywords: H42; H52; I20; J13; J21; J22; 330; mother's labor supply; preschool children; childcare; quasi-natural experiment; differences-in-differences-in-differences